Contents of Cd, Pb, Cr and Hg in sediments and the clam Corbicula subsulcata from some estuaries of central Vietnam - Minh, Vo Van; Khanh, Nguyen Van; Kinh, Kieu Thi; Phuong Anh, Vu Thi (Academia Journal of Biology, 2015)
This paper presents the results of concentration of heavy metals accumalated in sediments and in the clam Corbicula subsulcata at the estuaries in Central Region, Vietnam. In August 2012 and March 2013, samples of sediments and the clam Corbicula subsulcata were taken at 27 points as representatives for 3 research sites, including Thuan An, Cua Dai and Sa Can estuaries as derived from Huong river (Thua Thien Hue province), Thu Bon river (Quang Nam province) and Tra Bong river (Quang Ngai province), respectively. The results indicated that heavy metal concentration in sediments at most of the research points were lower than the national standards. However, heavy metal contents in the clam Corbicula subsulcata were higher than the level regulated for food safety by Vietnam Ministry of Health. Significant correlations were found between the heavy metal contents in sediment and in the muscle tissues of Corbicula subsulcata for Cd and Pb, respectively but low for Hg and Cr. These findings indicate that the species Corbicula subsulcata can be used as a bioindicator for monitoring the contamination of Cd and Pb in sediments in the estuaries in Central Vietnam.